Levels of polychlorinated biphenyls (PCBs) in human adipose tissue from Baghdad/Iraq. (1st October 2016) - Alawi, Mahmoud A.; Al-Tameemi, Firas T.
Abstract: The levels of 12 polychlorinated biphenyls (PCBs) in human adipose tissue samples gathered from patients, from three different hospitals, in Bagdad/Iraq were analyzed. All samples were extracted, cleaned up, and analyzed by GC/MS for dioxin-like PCBs. The total mean concentration of PCBs in all human adipose tissues samples was 404 μg/kg. Pentachlorobiphenyls were the predominant PCB congeners, accounting for 62.56% of the total PCB concentration found in the human adipose tissue samples which represent the most toxic compounds between all dioxin-like PCB congeners. The toxicity equivalents (TEQ PCBs) in all human adipose tissue samples were found in the range of 0.0126–86.284 μg TEQ/kg. The present average TEQ of 11.52 μg/kg is within the range that obtained by other studies.